Clima organizacional y el desempeño laboral de los trabajadores en la empresa inmobiliaria Romaan Innovation EIRL año 2024 - Oliva Puente, Valeria Susana (2025)
The objective of this research was to determine the relationship between organizational climate and job performance among the employees of the real estate company Romaan Innovation EIRL during the year 2024. The study was basic research with a quantitative approach, a descriptive-correlational level, and a non-experimental, cross-sectional design. The sample consisted of 30 employees, to whom a Likert-type questionnaire was administered individually and confidentially. The results obtained through Pearson's correlation test indicated a positive but very low, almost non-existent, relationship between organizational climate and job performance (r = 0.003), with a significance value of p = 0.986, which is greater than the 0.05 threshold. Therefore, neither the general hypothesis nor the specific ones were statistically validated, although some dimensions showed positive but extremely low trends. These findings suggest that, in the context of this organization, organizational climate is not significantly related to job performance. Nevertheless, the results provide a useful basis for identifying opportunities for improvement in internal management and for strengthening key dimensions such as communication, rewards, productivity, and training.